Parvovirus B19 infection and its role in rheumatology - G. I. Gridneva; B. S. Belov; M. S. Tolbeeva; E. S. Aronova (Современная ревматология)
The article summarizes modern data on the parvovirus (PV) B19 infection and associated conditions in rheumatological practice. Special attention is paid to the features of the structure and replication of the virus in infected cells of macroorganism, which contributes to a better understanding of the pathogenesis of the disease. The sequence of immune response formation during infection with PV B19 is considered. The issues of epidemiology of PV B19 infection, with outbreaks recorded approximately every 3 years, areraised. The possibility of a hemocontact route of transmission of PV B19 with IV drugs is emphasized. The course of PV B19 infection in immunosuppressed patients is described. The features of the clinical picture are presented and it is pointed out that the differential diagnosis of arthritis associated with PV B19 and rheumatoid arthritis is very difficult in the absence of the relevant epidemiological anamnesis.